Trends in disease characteristics and premature mortality among hospitalised middle-aged patients in Anhui Southern Area, China, between 2011 and 2020: a cross-sectional study - Chen Lei; Yao Yuanying; Lijuan Ma (BMJ Open)
Objectives We aimed to explore the characteristics of age, disease and premature mortality among middle-aged inpatients.Design Cross-sectional.Setting Data were gathered from the electronic medical records system of the hospitals between 2011 and 2020: a regional study.Participants A total of 151 320 patients, aged 45–59 years, underwent hospitalisation.Primary outcome measures We analysed the characteristics of age and disease using the database from the electronic medical record system. Moreover, a binary logistic regression model was adopted to investigate the risk factors for premature mortality.Results We identified 151 320 eligible inpatients, 53.0% of whom were female. The proportion of middle-aged inpatients increased alarmingly over a decade from 6.4% in 2011 to 28.3% in 2020. The incidence rate of inpatients aged 45 to 50 years increased perpendicularly, with its peak observed at the age of 50. The prevalence tended to decrease after the age of 50; however, it increased at the age of 59. Overall, cancer had the highest incidence rate (22.7%), followed by accidental injury, digestive system disease, cardiovascular disease and cerebrovascular disease (9.0%, 7.9%, 6.3% and 4.5%, respectively). The overall mortality among the middle-aged inpatients was 0.5%. Logistic regression analysis showed that sex, marital status and comorbidity were the factors contributing to mortality in hospitalised patients, with male, divorced and more than two comorbidities being risk factors for death.Conclusions A rising trend in the number of middle-aged inpatients was observed during the study period. The number of hospitalisations reaches its peak at the age of 50. Being male, divorced and having more than two comorbidities are risk factors for premature mortality. So prevention, early detection and appropriate treatment of comorbidities are beneficial in improving health and reducing mortality.